EDE TERÉNYI – THE MONO-OPERA “LA DIVINA COMMEDIA” – CONTENTS AND FORMS (I. PART – “INFERNO”) - COCA, Gabriela (Studia Universitatis Babes-Bolyai Musica, 2008)
Ede Terényi had come across the poetical work La Divina Commedia for the first time at the beginning of the 1970’s. As it was a turning point in his life as well, the work of Dante had a very sensitive influence in his own life as along thirty years of his life, the composer came back thorough his creations to this subject. His impressions were transposed both in a colour visual form – by creating a series of twenty-five pictures that were entitled Dantesca, and also in a musical sonorous form by composing the mono-opera La Divina Commedia. Not only this musical work but also many other musical works from the 1971-2004 have the print of the work of Dante. This study has the short and the analytical presentation of the mono-opera La Divina Commedia by the mirroring of the pictures in the series Dantesca that were signed by the composer.